Near integration, bank reluctance, and discount window borrowing - Dutkowsky, Donald H; McCoskey, Suzanne K (Journal of Banking & Finance, 2001)
This study puts forth stationarity considerations in explaining the observed breakdown between aggregate Discount Window borrowing and the spread between the Federal Funds rate and the discount rate during the post-1987 period. Tests with biweekly data indicate stationarity for adjustment borrowing, but cannot reject the unit root for the spread. The Goodfriend–Dutkowsky dynamic implicit cost formulation can accommodate the contrasting stationarity properties. Structural restrictions are compatible with stationary borrowing and a stationary or near integrated spread. While empirical findings from the static model indicate greater bank reluctance to borrow over time, the dynamic model gives considerably less support.